CHARACTERISTICS OF AUDIT COMMITTEES AND SUSTAINABILITY REPORTING - Rosmita Rasyid; Sparta; Billy Billy (Graduate Program of Universitas Tarumanagara, 2026)
This study aims to examine the influence of audit committee characteristics on sustainability reporting in financial institutions, particularly banking companies. The characteristics analyzed include audit committee size, the frequency of audit committee meetings held annually, and gender diversity among audit committee members, with firm size incorporated as a control variable. The sample consists of 62 observations from banking companies listed on the Indonesia Stock Exchange (IDX) that meet the research criteria for the years 2023 and 2024. Data were obtained from the banks’ annual reports for 2023–2024 and analyzed using multiple linear regression with the assistance of EViews software. The findings indicate that audit committee size has a positive effect on sustainability reporting. The frequency of audit committee meetings shows no influence on sustainability reporting. Gender diversity also demonstrates no significant effect; however, at a more relaxed significance threshold, gender diversity exhibits a negative relationship with sustainability reporting. These results imply that banking institutions should, first, ensure that audit committees consist of a sufficient number of members. Second, they should establish mechanisms that facilitate effective meetings with full attendance. Finally, there is a need to strengthen sustainability-related literacy and understanding—particularly among female audit committee members—to enhance their contribution to sustainability oversight.